Saint Paul : Master of the Spiritual Life in Christ"" - Maloney, Elliott C. (Book collections on Project MUSE., 2014)
In Saint Paul, Elliott C. Maloney explores what the great saint says about the spiritual life, the "how to" in the day-to-day activities and concerns of Christians. How should people live in covenant relationship with God, committed to seeking God's will in every aspect of their lives? Spirituality is a popular topic, but it is regarded as merely one part of life, some "higher level" of living when compared to ordinary living. Even Catholic scholarship, Maloney argues, notable as it is in Pauline exegesis and theology, seems to lack a feel for the overall kind of living that Paul wanted for his communities, not to mention how we might appropriate such wisdom for today. For Paul, all of a believer's life is spiritual life. The alternative is a life "according to the flesh," a self-centered life without God, a continual spiritual death.